Geodynamics and Geospatial Research: Conference Papers - University of Latvia 82nd International Scientific Conference (University of Latvia, 2024)
The conference “Geodynamics and Geospatial Research” organized by the Institute of Geodesy and Geoinformatics of the University of Latvia addresses a wide range of scientific studies and is focused on the interdisciplinarity, versatility and possibilities of research in this wider context in the future to reach more significant discoveries, including business applications and innovations in solutions for commer cial enterprises. The research presented at the conference is at different stages of its development and presents the achievements and the intended future. The publication is intended for researchers, students and research social partners as a source of current information and an invitation to join and support these studies.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics::Other physics::Geophysics; National Geodetic networks; photogrammetry; gravimetric and magnetic measurements; satellite geodesy; geoinformatics